Sustainable and Practical Superhydrophobic Surfaces via Mechanochemical Grafting - Nusret Celik; Serdar Akay; Furkan Sahin; Gulay Sezer; Esen Dagasan Bulucu; Mahmut Ruzi; Hans‐Jürgen Butt; Mustafa Serdar Onses (Advanced Materials Interfaces, 2023)
Abstract The broad adoption of superhydrophobic surfaces in practical applications is hindered by limitations of existing methods in terms of excessive usage of solvents, the need for tedious and lengthy chemical processes, insufficient biocompatibility, and the high cost of materials. Herein, a mechanochemical approach for practical and solvent‐free manufacturing of superhydrophobic surfaces is reported. This approach enables solvent‐free and ultra‐rapid preparation of superhydrophobic surfaces in a single‐step without the need for any washing, separation, and drying steps. The hydrolytic rupture of siloxane bonds and generation of free radicals induced by mechanochemical pathways play a key role in covalent grafting of silicone to the surface of nanoparticles that leads to superhydrophobic surfaces with a water contact angle of >165° and a sliding angle of <2°. The direct use of industrially available and non‐functional silicone materials together with demonstrated applicability to inorganic nanoparticles of varied composition greatly contribute to the scalability of the presented approach. The resulting superhydrophobic surfaces are highly biocompatible as demonstrated by fibroblast cells using two different assays. Monolith materials fabricated from silicone‐grafted nanoparticles exhibit bulk and durable superhydrophobicity. The presented approach offers tremendous potential with sustainability, scalability, cost‐effectiveness, simplicity, biocompatibility, and universality.